Linear and nonlinear preequalization - Simeone, O.
A transceiver structure for frequency-flat multiple-input multiple-output (MIMO) systems that comprises linear/nonlinear preequalization/equalization is optimized according to the minimum mean square error (MMSE) criterion under the assumption that only long-term channel state information (i.e., correlation matrices of fading channel and noise) is available at the transmitter. The structure generalizes different techniques known from the literature, such as BLAST, linear preequalization and equalization, and Tomlinson-Harashima precoding (THP). Simulations show that relevant benefits can be obtained by exploiting the long term channel state information at the transmitter in both dense multipath channels with relatively large correlation at the transmitter side and in sparse multipath channels.
Keywords: MIMO systems; MMSE criterion; Tomlinson-Harashima precoding; V-BLAST.; Long term channel state information; Minimum mean square error; Multipath channels; Multiple output multiple input; Multiple-input multiple output; Nonlinear preequalization; Radio transceiver; Radio transmitter